dBASE IV QuickStart - Metzelaar, Lawrence C. and Marianne B. Fox. (Carmel Que Corporation, 1989)
dBase IV QuickStart uses an exciting new approach to introduce the fundamental concepts of dBase IV to beginning users. Throughout the book, each sBase IV topic is presented in two or more pages of easy-to-follow text, followed by two or morepages of graphics. The graphics illustrate the topic discussed on the text pages.
Keywords: Teaching English